A Causal Model of Factors Influencing Adherence to Standard Precautions Practices Among Chinese Emergency Nurses: A Cross-sectional Study - Huang, Yanfang; Lertwatthanawilat, Wanchai; Klunklin, Pimpaporn; Unahalekhaka, Akeau (Pacific Rim International Journal of Nursing Research, 2024)
Standard precautions are essential to prevent cross-infections among emergency nurses, particularly during a pandemic of infectious diseases. However, poor adherence to such standard precautions is an ongoing global health system problem. This may be due to nurses’ lack of adequate understanding regarding the influencing mechanisms of various factors that cause cross-infection in practice. In this cross-sectional study, we rigorously utilized the Theory of Planned Behaviors as a guiding framework to develop and test a causal model of factors influencing adherence to standard precautions practices among Chinese emergency nurses. From July 2022 to February 2023, purposive sampling was used to recruit 310 emergency nurses from eight tertiary hospitals in four cities in Sichuan Province, China, during the COVID-19 pandemic. Research instruments included a Demographic Data Form, the Standard Precautions Questionnaire, the Leading Culture of Quality in Infection Prevention Scale, and the Compliance with Standard Precautions Scale. Data were analyzed using descriptive statistics and the Analysis of Moment Structure program to test the influencing factors. The final model of factors influencing adherence to standard precautions practices among Chinese emergency nurses explained 36% of the variance. This model provides a practical tool for understanding and improving adherence to standard precautions. Infection prevention climate and intention can affect adherence practices directly. In addition, nurses’ attitudes to standard precautions, social norms of standard precautions, perceived behavioral control of standard precautions, and infection prevention climate indirectly affected adherence practices through intention as the mediator. Among these factors, infection prevention climate had the most substantial effect on adherence practices. These findings underscore the pivotal role of nursing administrators in highlighting the remarkable benefits of standard precautions, shaping emergency nurses’ positive attitudes and confidence toward standard precautions, and creating a supportive climate for infection control. By implementing these strategies, nursing administrators can significantly improve adherence to standard precautions, ensuring a safer healthcare environment for workers, patients, and the public.